Catharsis - The real effects of bank insolvency and resolution - Josef Korte (Deutsche Bundesbank, 2013)
In general, banks play a growth-enhancing role for the real economy. However, distorted incentives for banks, depositors, and regulators in connection with bank insolvency may corrupt banks' credit allocation and monitoring decisions, leading to suboptimal real economic outcomes. A rules-based prompt resolution regime for insolvent banks may reestablish the incentive system and provide for economically superior credit allocation and monitoring. We test the hypothesis that regulatory insolvency has a cathartic effect using a large firm-level dataset and proposing a new indicator to measure the strength of catharsis. Employing an instrumental variable setup and an interaction approach, we try to overcome concerns about causality and potential endogeneity which are usually inherent to research into the real economic implications of bank regulation. We find a comparably stronger implementation of a hypothetical positive capital closure rule to have a positive and statistically as well as economically significant effect on individual firm growth - particularly for firms that are structurally more dependent on bank financing. Our findings are robust to various specifications. Investigating the transmission channels of the 'catharsis effect', we find that it essentially works through benefiting better quality firms and reallocating credit towards firms that need it most. Additional analyses suggest that the 'catharsis effect' works best in open banking systems that provide high access to international finance and, hence, mitigate potentially negative credit supply effects of insolvent bank liquidation. Taken together, our findings advocate stronger attention being given to incentive-compatible bank resolution regimes.
Keywords: G21; G28; G33; 330; bank insolvency; bank resolution; bank closure; bank regulation; finance and growth